Impact of Distributed Energy Resources on Fault Location, Isolation, and Service Restoration - Carneiro, Carlos Alberto [UNESP]; Silva, Gabriela Batista [UNESP]; Junior, Jairo Giacomini [UNESP]; Cebrian, Juan Carlos [UNESP]; Morales-Paredes, Helmo Kelis [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Currently, fault location, isolation and service restoration (FLISR) is a Smart Grid functionality used to improve the performance of electric utilities. This article investigates the impact of Distributed Power Resources (DER) on FLISR in terms of protection system failures and reliability indicators such as Average Interruption Frequency Index (SAIFI) and Average System Interruption Duration Index (SAIDI) and Unsupplied Energy (ENS). A probabilistic methodology based on the Monte Carlo method is performed to estimate these indicators with different penetration rates of DER (PR). The study is performed on 135 busbar distribution system. The results show that up to 156% PR, the protection system is not compromised. The insertion of REDs can bring an improvement in reliability indicators during higher solar radiation, however, they do not present relevant improvements in reliability indicators when FLISR is applied. This study can help electric utilities to plan investments in FLISR with different DPR.
Keywords: distributed generation; distribution system; FLISR; self-healing; smart grids